Měkkýši Národní přírodní rezervace Karlštejn v Českém krasu - Štěpánka Podroužková (Malacologica Bohemoslovaca, 2015)
This paper brings findings of recent malacological research (2013) and earlier mostly unpublished data about malacofauna of the Karlštejn National Nature Reserve (abbreviated as NNR) (Czech Republic, Central Bohemia, Bohemian Karst Protected Landscape Area). A total of 89 mollusc species (76 terrestrial snails, 5 freshwater snails, 8 bivalves) were recorded. The mollusc fauna of the NNR represents 35% of the total of 251 mollusc species found in the Czech Republic. The studied area comprises of very diverse habitat types with various and rich mollusc communities. Forest snails are dominating (38%) followed by species of the open steppes (27%). 28 species belong to endangered Red List species of the Czech Republic. Critically endangered Helicopsis striata and endangered Chondrina avenacea, Truncatellina claustralis and Zebrina detrita belong to the species of dry and open habitats. Helicopsis striata is probably extincted in most of localities in the Bohemian Karst. Its presence in the NNR was not confirmed. Bohemian Karst holds most of populations of Chondrina avenacea in the Czech Republic and the most of findings are situated in the Karlštejn NNR. Zebrina detrita inhabits here isolated site in Bohemia, where it was probably introduced in the past. Four new sites of the Holocene optimum relict Truncatellina claustralis were found.